Effects of drug treatment on hypertension and cardiac hypertrophy in spontaneously hypertensive rats - Ruskoaho, Heikki (Oulu : University of Oulu : Oulu University Library, [distr.], 1983)
Abstract.
Väitöskirja
Väitöskirja
Keywords: hypertensive agents; heart enlargement -- drug therapy; hypertension; rats; Antihypertensive Agents; Cardiomegaly -- drug therapy; antihypertensive drugs; blood pressure; reversal of cardiac hypertrophy; catecholamines; cardiovascular reactivity; baroflex sensitivity; Academic Dissertation; väitöskirjat; doktorsavhandlingar